THE MANAGEMENT OF PRIVATIZATION - Godzich, Wlad (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1993)
A study of the constitution of the modern subject at the end of the Middle Ages. Godzich argues that this is accomplished through the privatization of the collective memoria into a social imaginary made up of individual consciousnesses. This is traced with particular reference to the problem of genre and of fiction in Don Quijote.